Selective hydrogenation catalyst for phenylacetylene in crude styrene and application thereof

By using Pd and Pt, rare earth elements and IB elements as catalysts in the hydrogenation catalyst, combined with ɑ-alumina or quartz as support, the specific surface area of ​​the catalyst components and support is adjusted, the removal of phenylacetylene in the ethylbenzene dehydrogenation process is solved. The problem of poor results has achieved efficient phenylacetylene removal and low styrene loss rate.

CN119318972APending Publication Date: 2025-01-17XINNUO CHEM TECH (TAIXING) CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411439027.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-15
Publication Date
2025-01-17

AI Technical Summary

Technical Problem

The removal effect of phenylacetylene in crude styrene prepared in the ethylbenzene dehydrogenation process is not ideal, and the loss rate to styrene is high, which cannot meet the requirements of high removal rate and low loss rate.

Method used

The carrier is 97.5%-99% of Pd and Pt, 0.2-1% of rare earth elements or their oxides and 0.2-1% of IB, IIB elements or their oxides as cocatalysts. Selective hydrogenation catalysts for alumina or quartz improve the hydrogenation efficiency of phenylacetylene and reduce the hydrogenation rate of styrene by adjusting the specific surface area of ​​the support and the component ratio of the catalyst.

Benefits of technology

The conversion rate of phenylacetylene in crude styrene reached more than 99.2%, and the loss rate of styrene was reduced to the highest 0.7%, meeting the requirements of high removal rate and low loss rate.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119318972A_ABST
    Figure CN119318972A_ABST
Patent Text Reader

Abstract

The invention provides a selective hydrogenation catalyst for phenylacetylene in crude styrene. The selective hydrogenation catalyst comprises the following components in percentage by weight: a main catalyst: 0.1-1.0% of at least one of Pd and Pt; a promoter A: 0.2-1% of a rare earth element or an oxide thereof; a promoter B: 0.2-1% of at least one element selected from IB and IIB in the periodic table of elements or an oxide thereof; and a carrier: 97.5%-99% of at least one of alpha-alumina or quartz. The invention also discloses an application of the selective hydrogenation catalyst in catalytic hydrogenation of phenylacetylene in crude styrene, wherein the crude styrene is collected by an ethylbenzene dehydrogenation industrial device. According to the invention, alpha-alumina and quartz are adopted as carriers, and a high-proportion carrier is adopted, so that the reaction speed is reduced, and hydrogenation of styrene is avoided as much as possible under the condition of meeting phenylacetylene hydrogenation. Meanwhile, the effective components of the catalyst adopt composite components, and the mutual coordination effect among the catalytic components is utilized, so that the hydrogenation of phenylacetylene is improved, and the hydrogenation of styrene is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a selective hydrogenation catalyst for phenylacetylene in crude styrene and application of the selective hydrogenation catalyst. Background Art

[0002] Styrene is mainly used to synthesize polystyrene, expanded polystyrene, acrylonitrile-butadiene-styrene copolymer, styrene-butadiene rubber, etc. Styrene is usually prepared by dehydrogenation of ethylbenzene, accompanied by the production of a small amount of phenylacetylene. The reaction mixture formed after the dehydrogenation of ethylbenzene is called crude styrene. The phenylacetylene contained in crude styrene is an undesirable component. The presence of phenylacetylene will not only increase the catalyst consumption during the anionic polymerization of styrene, which is harmful to the chain growth and polymerization rate, but also the unreacted phenylacetylene in polystyrene will lead to poor product performance, such as discoloration, degradation, taste change and release of odor, so it is necessary to remove phenylacetylene as much as possible.

[0003] When phenylacetylene in crude styrene is selectively hydrogenated and removed, the main components of the hydrogenation catalyst used include precious metals and non-precious metals, among which the precious metals mainly include Pd, Pt, Ag, Au, Rh, etc., and the non-precious metals mainly include Cu, Zn, Ni, Fe, Co, etc. The carrier used is mainly porous materials such as γ-alumina and activated carbon.

[0004] The existing hydrogenation catalyst has high activity and can well complete the hydrogenation removal of phenylacetylene. When hydrogenating phenylacetylene, the desired product is styrene, but if it is over-hydrogenated, styrene will return to ethylbenzene. At present, the conditions for the hydrogenation reaction of phenylacetylene are basically based on a temperature of 60°C and a pressure of 0.2-0.21Mpa. The temperature of the hydrogenation reaction is relatively high, and the hydrogenation rate of phenylacetylene is about 70%, accompanied by a loss of about 3% of styrene.

[0005] In recent years, with the development of ethylene industry and the large-scale development, the technology of extracting and recovering styrene from pyrolysis gasoline has also become one of the production methods of styrene. The crude styrene recovered from pyrolysis gasoline also contains a certain amount of phenylacetylene, and it is also necessary to carry out hydrogenation to remove phenylacetylene. When the crude styrene produced by pyrolysis gasoline is hydrogenated to remove phenylacetylene, the catalyst used is nickel element as the main catalyst, rare earth and the middle element in IB, IIB, VIB or VIIB as the co-catalyst, and the carrier is a composite carrier of aluminum oxide and silicon oxide. When the catalyst is used for the crude styrene produced by pyrolysis gasoline, it has a good removal effect on phenylacetylene, and the loss rate of styrene is up to 2.1% and the lowest is -0.5%. However, when the catalyst is used for the crude styrene prepared by dehydrogenation of ethylbenzene, the desired high removal rate of phenylacetylene and the low loss rate of styrene are not reflected. The reason may be that the crude styrene produced by the two processes has a large difference in composition. The crude styrene produced by the ethylbenzene dehydrogenation process contains 50-75% styrene and 22-45% ethylbenzene, and contains 40-150ppm of phenylacetylene; while the crude styrene recovered from pyrolysis gasoline contains about 40% styrene and about 10% ethylbenzene, which shows that the composition of crude styrene produced by pyrolysis gasoline is more complex, so that the same catalyst shows different removal effects when removing phenylacetylene from different types of crude styrene.

[0006] Therefore, there is still a need to find a hydrogenation catalyst with better selectivity for phenylacetylene in the production of crude styrene from ethylbenzene. Summary of the invention

[0007] In order to solve the problem of unsatisfactory removal of phenylacetylene in crude styrene prepared by dehydrogenation of ethylbenzene in the prior art, the present application firstly proposes a selective hydrogenation catalyst for phenylacetylene in crude styrene, which comprises the following components in weight percentage:

[0008] Main catalyst: 0.1-1.0% of at least one of Pd and Pt; co-catalyst A: 0.2-1% of rare earth elements or their oxides; co-catalyst B: 0.2-1% of at least one element selected from IB and IIB in the periodic table or its oxides; carrier: 97.5%-99% of at least one of α-alumina or quartz.

[0009] The inventors of the present application have found in the course of their research that the type of catalyst carrier and the specific surface area have a great influence on the hydrogenation effect of phenylacetylene. In the existing catalysts, more emphasis is placed on the specific type of catalyst and the ratio of the catalytic components, and less design is given to the type of carrier, the pore structure and the specific surface area. In a patent entitled "Method for Selective Hydrogenation of Phenylacetylene" (Patent No. 2004800221988), it is proposed to load the catalytic components on a θ-alumina carrier and use it for the removal of phenylacetylene from crude styrene prepared by dehydrogenation of ethylbenzene. The phenylacetylene hydrogenation rate is as low as about 70%, and the styrene loss rate is about 3%.

[0010] In the prior art, in order to improve the hydrogenation efficiency, the main goal is to increase the reaction rate. After research, the inventors of the present application believe that increasing the reaction rate can improve the hydrogenation efficiency of phenylacetylene, but it will also improve the hydrogenation efficiency of styrene. The alumina carrier of the existing hydrogenation catalyst is mainly δ alumina and γ alumina, wherein the specific surface area of ​​δ alumina is 90-200m 2 / g, the specific surface area of ​​γ-alumina reaches 200-300m 2 / g, the increase in specific surface area is conducive to the diffusion of reactants, increases hydrogenation efficiency, and can accelerate the reaction rate, but at the same time it gives styrene greater power to be hydrogenated into ethylbenzene, resulting in an increase in the loss rate of styrene.

[0011] In the present application, α-alumina and quartz are used as carriers, and the proportion of the carrier in the catalyst is greatly increased to reduce the proportion of the effective component in the catalyst, thereby reducing the reaction speed, and avoiding the hydrogenation of styrene as much as possible under the condition of satisfying the hydrogenation of phenylacetylene. At the same time, the active ingredient of the catalyst adopts a composite component, in addition to the main catalyst, a cocatalyst A and a cocatalyst B are also compounded, and the mutual coordination between each catalytic component is utilized to reduce the hydrogenation of styrene under the condition of improving the hydrogenation of phenylacetylene. Using the catalyst in the present application, the conversion rate of phenylacetylene in crude styrene can be made to reach more than 99.2%, and the loss rate of styrene is only 0.7% at the highest.

[0012] Specifically, the specific surface area of ​​the carrier is 1-50m 2 / g. Under the above specific surface area, phenylacetylene can be smoothly hydrogenated, while the hydrogenation rate of styrene is reduced. When the specific surface area is too low, the catalytic efficiency is too low, resulting in too low reaction efficiency, thereby increasing production costs. When the specific surface area is too high, the catalyst components loaded are excessive, which easily leads to a violent reaction rate. Although the hydrogenation of phenylacetylene can be guaranteed, it also leads to the hydrogenation of styrene, increasing the loss rate of styrene.

[0013] Furthermore, in order to ensure the reaction efficiency and reduce the loss rate of styrene, the total amount of the co-catalyst A and the co-catalyst B is 0.6-2.0%.

[0014] Further, the selective hydrogenation catalyst is prepared by the following steps:

[0015] (1) calcining and crystallizing the carrier raw material at 1200-1250° C. to form a carrier;

[0016] (2) impregnating the support into a catalyst impregnation solution, and after the impregnation is completed, drying and calcining are performed to prepare;

[0017] The catalyst impregnation liquid includes a soluble complex of the main catalyst, a soluble salt of the promoter A, and a soluble salt of the promoter B. The soluble complex of the main catalyst is specifically a palladium ammonia complex and a platinum ammonia complex, and the soluble salt of the promoter A and the soluble salt of the promoter B are specifically nitrates, sulfates, or chlorides. In the preparation process, a calcination temperature of 1200-1250°C is used. At this calcination temperature, the crystal form of alumina is α-Al2O3, and within this temperature range, the linear shrinkage of alumina is small, which is mainly reflected in the dislocation activity between ions, which can ensure that the specific surface area of ​​the carrier is at a low level, but still has an appropriate amount of pores. When the calcination temperature exceeds 1250°C, the grains of alumina begin to shrink significantly, causing the pores to be greatly reduced, and it is impossible to load an appropriate amount of catalyst components. When the calcination temperature is too low, the alumina is still in the θ crystal form or the k crystal form, which makes the pores in the carrier too large.

[0018] Specifically, to ensure the loading amount of the catalyst, in step (2), the total concentration of the catalyst impregnation solution is 0.5-10wt%, the impregnation temperature is 20-100°C, and the impregnation time is 0.5-10h. The total concentration of the catalyst impregnation solution is further preferably 3-7%, the impregnation temperature is further preferably 50-80°C, and the impregnation time is further preferably 0.5-2h.

[0019] Specifically, in order to stably attach the catalytic component to the carrier, in step (2), the drying temperature is 100-150°C, the drying time is 2-10 hours, the calcination temperature is 400-700°C, and the calcination time is 2-6 hours. The drying temperature of 100-150°C is preferably 100-120°C, and the drying time is more preferably 3-6 hours. The calcination temperature is more preferably 500-600°C, and the calcination time is more preferably 3-5 hours.

[0020] Secondly, the present application also proposes the use of any of the above-mentioned selective hydrogenation catalysts in the catalytic hydrogenation of phenylacetylene in crude styrene, that is, the crude styrene in the present application is obtained from an ethylbenzene dehydrogenation industrial device.

[0021] Specifically, the crude styrene comprises the following components: 50-75% styrene, 22-45% ethylbenzene, 40-150 ppm phenylacetylene and 2.9-5% others, wherein the others are specifically benzene, toluene, methane, ethane, propane and other components generated by side reactions during the dehydrogenation of ethylbenzene.

[0022] Furthermore, in order to adapt to the above selective hydrogenation catalyst to better hydrogenate phenylacetylene, the catalytic hydrogenation process of phenylacetylene is as follows: reaction temperature 58-65°C, pressure: 2.7-3.2Mpa, space velocity 0.4-0.6h -1 , gas-liquid ratio (18-25):1. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 This is a diagram showing the effect of using the selective hydrogenation catalyst in Example 1.

[0024] Figure 2 This is a diagram showing the effect of using the selective hydrogenation catalyst in Comparative Example 7. DETAILED DESCRIPTION

[0025] Example 1

[0026] Pseudo-boehmite was formed into strips by adding nitric acid and calcined at 1200℃ for 4h to form α-alumina carrier, which was used as carrier No. 1 with a BET of 16.5m 2 / g.

[0027] 8.00g of palladium-ammine complex (containing 1wt% Pd), 8.00g of ammonia water, 0.374g of lanthanum nitrate hexahydrate and 0.462g of copper nitrate trihydrate were used to prepare a catalyst impregnation solution with a total concentration of 4g / L. 39.80g of carrier No. 1 was impregnated in the catalyst impregnation solution at 50°C for 1 hour, dried at 100°C for 6 hours, and calcined at 500°C for 4 hours to prepare a selective hydrogenation catalyst, numbered JH-01. JH-01 contains 0.2wt% Pd, 0.3wt% Cu and 0.3wt% lanthanum.

[0028] Example 2

[0029] Pseudo-boehmite was formed into strips by adding nitric acid and calcined at 1250℃ for 4h to form α-alumina carrier, which was used as carrier 2 with a BET of 16.2m 2 / g.

[0030] 8.00g of palladium-ammine complex (containing 1% Pd), 8.00g of ammonia water, 0.374g of lanthanum nitrate hexahydrate and 0.189g of silver nitrate were taken to prepare a catalyst impregnation solution with a total concentration of 6g / L. 39.68g of carrier No. 2 was taken, and after being immersed in the catalyst impregnation solution at 60°C for 2 hours, it was dried at 120°C for 3 hours, and then calcined at 600°C for 3 hours to prepare a selective hydrogenation catalyst, numbered: JH-02. JH-02 contains 0.2%wtPd, 0.3wt%Ag, and 0.3wt%lanthanum.

[0031] Example 3

[0032] Pseudo-boehmite was formed into strips by adding nitric acid and calcined at 1210℃ for 4h to form α-alumina carrier, which was used as carrier No. 3 with a BET of 16.3m 2 / g.

[0033] 8.00g of palladium-ammine complex (containing 1% Pd), 8.00g of ammonia water, 0.462g of lanthanum nitrate hexahydrate, and 0.623g of copper nitrate trihydrate were used to prepare a catalyst impregnation solution with a total concentration of 7g / L. 39.60g of carrier No. 3 was impregnated in the catalyst impregnation solution at 80°C for 1.5 hours, dried at 110°C for 5 hours, and calcined at 600°C for 5 hours to prepare a selective hydrogenation catalyst, numbered JH-03. JH-03 contains 0.2wt% Pd, 0.3wt% Cu, and 0.5wt% lanthanum.

[0034] Example 4

[0035] Pseudo-boehmite was added with nitric acid to form strips, and then calcined at 1240℃ for 4h to form α-alumina carrier, which was used as carrier 4#, with a BET of 16.8m 2 / g.

[0036] 8.00g of palladium-ammine complex (containing 1% Pd), 8.00g of ammonia water, 1.247g of lanthanum nitrate hexahydrate and 0.462g of copper nitrate trihydrate were taken to prepare a catalyst impregnation solution with a total concentration of 6g / L, 39.40g of carrier No. 4 was taken, and after being immersed in the catalyst impregnation solution at 55°C for 0.5 hours, it was dried at 120°C for 6 hours, and then calcined at 550°C for 3.5 hours to prepare a selective hydrogenation catalyst, numbered: JH-04. JH-04 contains 0.2wt% Pd, 0.3wt% Cu and 1.0wt% lanthanum.

[0037] Example 5

[0038] Pseudo-boehmite was added with nitric acid to form strips, and then calcined at 1200℃ for 4h to form α-alumina carrier, which was used as carrier No. 5 with a BET of 17.1m 2 / g.

[0039] 8.00g of palladium-ammine complex (containing 1% Pd), 8.00g of ammonia water, 0.623g of lanthanum nitrate hexahydrate and 0.769g of copper nitrate trihydrate were taken to prepare a catalyst impregnation solution with a total concentration of 5g / L, 39.52g of 5# carrier was taken, and after being immersed in the catalyst impregnation solution at 60°C for 1.5 hours, it was dried at 100°C for 5 hours, and then calcined at 580°C for 4 hours to prepare a selective hydrogenation catalyst, numbered: JH-05. JH-05 contains 0.2wt% Pd, 0.5wt% Cu and 0.5wt% lanthanum.

[0040] Example 6

[0041] Pseudo-boehmite was formed into strips by adding nitric acid and calcined at 1200℃ for 4h to form α-alumina carrier, which was used as carrier 6 with a BET of 16.0m 2 / g.

[0042] 8.00g of palladium-ammine complex (containing 1% Pd), 8.00g of ammonia water, 0.623g of lanthanum nitrate hexahydrate and 0.154g of copper nitrate trihydrate were taken to prepare a catalyst impregnation solution with a total concentration of 3g / L, 39.68g of 6# carrier was taken, and after being immersed in the catalyst impregnation solution at 65°C for 2 hours, it was dried at 105°C for 4 hours, and then calcined at 510°C for 4.5 hours to prepare a selective hydrogenation catalyst, numbered: JH-06. JH-06 contains 0.2wt% Pd, 0.1wt% Cu, and 0.5wt% lanthanum.

[0043] Example 7

[0044] Pseudo-boehmite was formed into strips by adding nitric acid and calcined at 1220℃ for 4h to form α-alumina carrier, which was used as carrier 7# with a BET of 17m 2 / g.

[0045] 6.00g of palladium-ammine complex (containing 1% Pd), 8.00g of ammonia water, 0.623g of lanthanum nitrate hexahydrate and 0.462g of copper nitrate trihydrate were taken to prepare a catalyst impregnation solution with a total concentration of 3.5g / L, 39.62g of 7# carrier was taken, and after being immersed in the catalyst impregnation solution at 50°C for 0.5 hour, it was dried at 125°C for 5 hours, and then calcined at 590°C for 3.5 hours to prepare a selective hydrogenation catalyst, numbered: JH-07. JH-07 contains 0.15wt% Pd, 0.3wt% Cu and 0.5wt% lanthanum.

[0046] Example 8

[0047] Pseudo-boehmite was formed into strips by adding nitric acid and calcined at 1220℃ for 4h to form α-alumina carrier, which was used as carrier 8 with a BET of 17.1m 2 / g.

[0048] 12.00g of palladium-ammine complex (containing 1% Pd), 8.00g of ammonia water, 0.623g of lanthanum nitrate hexahydrate and 0.462g of copper nitrate trihydrate were taken to prepare a catalyst impregnation solution with a total concentration of 5g / L, 39.56g of 8# carrier was taken, and after being immersed in the catalyst impregnation solution at 75°C for 2 hours, it was dried at 100°C for 3 hours and then calcined at 510°C for 3 hours to prepare a selective hydrogenation catalyst, numbered: JH-08. JH-08 contains 0.3wt% Pd, 0.3wt% Cu and 0.5wt% lanthanum.

[0049] Example 9

[0050] Pseudo-boehmite + silica 1:1 was added with nitric acid to form strips, and then calcined at 1200℃ for 4h to form an α-alumina silica mixed carrier as carrier 9#, with a BET of 20.4m 2 / g.

[0051] 8.00g of palladium-ammine complex (containing 1% Pd), 8.00g of ammonia water, 0.462g of lanthanum nitrate hexahydrate and 0.623g of copper nitrate trihydrate were taken to prepare a catalyst impregnation solution with a total concentration of 7g / L, 39.60g of 9# carrier was taken, and after being immersed in the catalyst impregnation solution at 80°C for 0.5 hour, dried at 120°C for 4 hours, and then calcined at 550°C for 5 hours, a selective hydrogenation catalyst numbered: JH-09 was prepared. JH-09 contains 0.2wt% Pd, 0.3wt% Cu, and 0.5wt% lanthanum.

[0052] Example 10

[0053] The silica sol was formed into strips and calcined at 1200℃ for 4h to form a silicon oxide carrier as carrier 10#. The BET analysis showed that the silica sol had a density of 6.5m 2 / g.

[0054] 8.00g of palladium-ammine complex (containing 1% Pd), 8.00g of ammonia water, 0.462g of lanthanum nitrate hexahydrate and 0.623g of copper nitrate trihydrate were taken to prepare a catalyst impregnation solution with a total concentration of 6g / L, 39.60g of 10# carrier was taken, and after being immersed in the catalyst impregnation solution at 55°C for 1.5 hours, it was dried at 110°C for 6 hours, and then calcined at 545°C for 3 hours to prepare a selective hydrogenation catalyst, numbered: JH-10. JH-10 contains 0.2wt% Pd, 0.3wt% Cu, and 0.5wt% lanthanum.

[0055] Comparative Example 1

[0056] Pseudo-boehmite was formed into strips by adding nitric acid and calcined at 1200℃ for 4h to form α-alumina carrier, which was used as carrier 11# with a BET of 16.6m 2 / g.

[0057] 8.00g of palladium-ammine complex (containing 1% Pd) and 8.00g of ammonia water were taken to prepare a catalyst impregnation solution with a total concentration of 5g / L, 39.92g of 11# carrier was taken, and after being immersed in the catalyst impregnation solution at 75°C for 1 hour, it was dried at 100°C for 6 hours, and then calcined at 550°C for 5 hours to prepare a selective hydrogenation catalyst, numbered: JH-11. JH-11 contains 0.2wt% Pd.

[0058] Comparative Example 2

[0059] Pseudo-boehmite was formed into strips by adding nitric acid and calcined at 1200℃ for 4h to form α-alumina carrier, which was used as carrier 12# with a BET of 16.4m 2 / g.

[0060] 8.00g of palladium-ammine complex (containing 1% Pd), 8.00g of ammonia water, and 0.462g of copper nitrate trihydrate were taken to prepare a catalyst impregnation solution with a total concentration of 3g / L, and 39.92g of 12# carrier was taken, and after being immersed in the catalyst impregnation solution at 55°C for 2 hours, it was dried at 120°C for 5 hours, and then calcined at 590°C for 5 hours to prepare a selective hydrogenation catalyst, numbered: JH-12. JH-12 contains 0.2wt% Pd and 0.3wt% Cu.

[0061] Comparative Example 3

[0062] Pseudo-boehmite was formed into strips by adding nitric acid and calcined at 1200℃ for 4h to form α-alumina carrier, which was used as carrier 13# with a BET of 16.5m 2 / g.

[0063] 8.00g of palladium-ammine complex (containing 1% Pd), 8.00g of ammonia water, and 0.374g of lanthanum nitrate hexahydrate were taken to prepare a catalyst impregnation solution with a total concentration of 4g / L, and 39.80g of 13# carrier was taken, and after being immersed in the catalyst impregnation solution at 70°C for 1.5 hours, it was dried at 115°C for 5 hours, and then calcined at 500°C for 3 hours to prepare a selective hydrogenation catalyst, numbered: JH-13. JH-13 contains 0.2wt% Pd and 0.3wt% lanthanum.

[0064] Comparative Example 4

[0065] Pseudo-boehmite was formed into strips by adding nitric acid and calcined at 500℃ for 4h to form a γ-alumina carrier as carrier 14# with a BET of 220m 2 / g.

[0066] 8.00g of palladium-ammine complex (containing 1% Pd), 8.00g of ammonia water, 0.462g of lanthanum nitrate hexahydrate and 0.623g of copper nitrate trihydrate were taken to prepare a catalyst impregnation solution with a total concentration of 6g / L, 39.60g of 14# carrier was taken, and after being immersed in the catalyst impregnation solution at 80°C for 2 hours, it was dried at 120°C for 6 hours, and then calcined at 600°C for 3.5 hours to prepare a selective hydrogenation catalyst, numbered: JH-14. JH-14 contains 0.2wt% Pd, 0.3wt% Cu, and 0.5wt% lanthanum.

[0067] Comparative Example 5

[0068] Pseudo-boehmite was formed into strips by adding nitric acid and calcined at 900℃ for 2h to form delta alumina carrier, which was used as carrier 15# with a BET of 50m 2 / g.

[0069] 8.00g of palladium-ammine complex (containing 1% Pd), 8.00g of ammonia water, 0.462g of lanthanum nitrate hexahydrate and 0.623g of copper nitrate trihydrate were taken to prepare a catalyst impregnation solution with a total concentration of 7g / L, 39.60g of 15# carrier was taken, and after being immersed in the catalyst impregnation solution at 55°C for 1 hour, it was dried at 115°C for 5 hours, and then calcined at 560°C for 4.5 hours to prepare a selective hydrogenation catalyst, numbered: JH-15. JH-15 contains 0.2wt% Pd, 0.3wt% Cu, and 0.5wt% lanthanum.

[0070] Comparative Example 6

[0071] Pseudo-boehmite was formed into strips by adding nitric acid and calcined at 1050℃ for 2h to form the θ alumina carrier as 16# carrier with BET of 24m 2 / g.

[0072] 8.00g of palladium-ammine complex (containing 1% Pd), 8.00g of ammonia water, 0.462g of lanthanum nitrate hexahydrate and 0.623g of copper nitrate trihydrate were taken to prepare a catalyst impregnation solution with a total concentration of 5g / L, 39.60g of 16# carrier was taken, and after being immersed in the catalyst impregnation solution at 75°C for 0.5 hour, it was dried at 110°C for 3 hours, and then calcined at 600°C for 5 hours to prepare a selective hydrogenation catalyst, numbered: JH-16. JH-16 contains 0.2wt% Pd, 0.3wt% Cu, and 0.5wt% lanthanum.

[0073] Comparative Example 7

[0074] The corresponding catalyst was prepared according to Example 1 in Patent No. 201110045258.X (named: Catalyst for the selective hydrogenation of phenylacetylene in the presence of styrene). Since the sintering temperature or type of alumina is not specified in the application, the alumina in this comparative example is sintered at a conventional sintering temperature of 850°C to prepare delta alumina, and then the delta alumina and silicon oxide are prepared in a weight ratio of 5:1 to prepare a composite carrier. 20 grams of the composite carrier is added to a solution with a nickel nitrate content of 12%, a lanthanum nitrate content of 3%, and a zinc nitrate content of 1%, and an equal amount of impregnation is performed, dried at 120°C for 6 hours, and calcined at 400°C for 8 hours to obtain a nickel-based catalyst A, so that the nickel content is 8% of the weight of the carrier, the lanthanum content is 0.2%, and the zinc content is 0.2%. The above-prepared catalyst is reduced with hydrogen at 300°C for 6 hours. No.: JH-17.

[0075] The catalytic performance of the selective hydrogenation catalysts prepared in the above examples and comparative examples was tested. During the test, the reaction conditions were as follows: temperature: 60°C, pressure: 3 MPa, space velocity: 0.5 h -1 , gas-liquid ratio 20:1.

[0076] The crude styrene obtained from the ethylbenzene dehydrogenation industrial device is used as the raw material. The composition of the crude styrene is as follows: 39.06wt% ethylbenzene, 57.66wt% styrene, 40ppm phenylacetylene, and the rest are other components. The test data are listed in Table 1. In Table 1:

[0077] Phenylacetylene conversion rate % = (phenylacetylene in the raw material - phenylacetylene in the product) / phenylacetylene in the raw material * 100%;

[0078] Styrene loss rate % = (styrene in product - styrene in raw material) / styrene in raw material * 100%.

[0079]

[0080] It can be seen from Table 1 that when the catalyst only contains cocatalyst A or cocatalyst B, the conversion rate of phenylacetylene can reach more than 99%, but the loss rate of styrene increases significantly. The specific surface area of ​​the carrier in Comparative Example 4 is relatively high. Although phenylacetylene can be completely converted, a large amount of styrene is lost. In Comparative Example 5, although the specific surface area of ​​the carrier is at the upper limit, since the carrier is δ alumina, a large amount of styrene is lost. In Comparative Example 6, compared with Example 9, although the specific surface area is at a normal level, the conversion rate of phenylacetylene is lower, and the loss of styrene is also improved, indicating that alumina of different crystal forms, even if their specific surface areas are at the same level, have different catalytic efficiencies and selectivities. The catalyst in Comparative Example 7 is based on the catalyst in the existing patent. Although the catalyst has good selectivity for phenylacetylene in crude styrene recovered from pyrolysis gasoline, its selectivity is reduced to a certain extent when used in producing crude styrene from ethylbenzene. The reason may be that the composition of crude styrene produced by the two processes is quite different, and the content and variety of by-products in the two crude styrenes are quite different, which may have different effects on the reaction process. In addition, when crude styrene is directly recovered from pyrolysis gasoline, it will contain trace amounts of cracking catalysts, which will also have a certain impact on the reaction of phenylacetylene.

[0081] In order to detect the effect of the catalyst, the effect of the selective hydrogenation catalyst in Example 1 and Comparative Example 7 was compared to obtain Figure 1 and Figure 2 As shown in the attached figure, when comparing the effects, the reaction conditions are: temperature: 60°C, pressure: 3Mpa, air velocity 0.5h -1 , gas-liquid ratio 20:1.

[0082] Figure 1 and Figure 2 The black data lines represent the conversion rate of phenylacetylene, and the red data lines represent the loss rate of styrene. Figure 1 and Figure 2 It can be seen that the selective hydrogenation catalysts in Example 1 and Comparative Example 7 remain stable during use, but the phenylacetylene conversion rate of Comparative Example 7 is lower than that of Example 1, and the styrene loss rate of Comparative Example 7 is higher than that of Example 1, indicating that the catalyst prepared in the present application is more suitable for the removal of phenylacetylene from crude styrene prepared by the ethylbenzene dehydrogenation process.

[0083] Similar results were obtained when the composition of crude styrene was adjusted within the following limits: 50-75% styrene, 22-45% ethylbenzene, 40-150 ppm phenylacetylene and 2.9-5% others.

[0084] The following adjustments are made in the catalytic hydrogenation process of phenylacetylene: reaction temperature 58-65°C, pressure: 2.7-3.2Mpa, space velocity 0.4-0.6h -1 , gas-liquid ratio (18-25): 1, similar results were obtained.

Claims

1. A catalyst for the selective hydrogenation of phenylacetylene in crude styrene, characterized in that: The composition comprises the following weight percentages: Main catalyst: 0.1-1.0% of at least one of Pd and Pt; Promoter A: 0.2-1% of rare earth elements or their oxides; Promoter B: 0.2-1% of at least one element selected from IB and IIB in the periodic table or its oxide; Support: at least one of 97.5%-99% α-alumina or quartz.

2. The selective hydrogenation catalyst according to claim 1, characterized in that The specific surface area of ​​the carrier is 1-50m 2 / g.

3. The selective hydrogenation catalyst according to claim 1, characterized in that The total amount of the promoter A and the promoter B is 0.6-2.0%.

4. The selective hydrogenation catalyst according to any one of claims 1 to 3, characterized in that The selective hydrogenation catalyst is prepared by the following steps: (1) calcining and crystallizing the carrier raw material at 1200-1250° C. to form a carrier; (2) impregnating the support into a catalyst impregnation solution, and after the impregnation is completed, drying and calcining are performed to prepare; The catalyst impregnation liquid includes a soluble complex of the main catalyst, a soluble salt of the co-catalyst A and a soluble salt of the co-catalyst B.

5. The selective hydrogenation catalyst according to claim 4, characterized in that In step (2), the total concentration of the catalyst impregnation solution is 0.5-10wt%, the impregnation temperature is 20-100°C, and the impregnation time is 0.5-10h.

6. The selective hydrogenation catalyst according to claim 4, characterized in that In step (2), the drying temperature is 100-150° C., the drying time is 2-10 hours, the roasting temperature is 400-700° C., and the roasting time is 2-6 hours.

7. Use of the selective hydrogenation catalyst according to any one of claims 1 to 6 in the catalytic hydrogenation of phenylacetylene in crude styrene, characterized in that: The crude styrene is produced by an ethylbenzene dehydrogenation industrial unit.

8. The use according to claim 7, characterized in that: The crude styrene comprises the following components: 50-75% styrene, 22-45% ethylbenzene, 40-150 ppm phenylacetylene and 2.9-5% others.

9. The use according to claim 7, characterized in that: The catalytic hydrogenation process of phenylacetylene is as follows: reaction temperature 58-65°C, pressure: 2.7-3.2Mpa, space velocity 0.4-0.6h -1 , gas-liquid ratio (18-25):1.

Citation Information

Patent Citations

  • Catalyst for selective hydrogenation of phenylacetylene in presence of styrene

    CN102649063A